Bilateral Lung Transplantation for Patients With Destroyed Lung and Asymmetric Chest Deformity - Yue, Bingqing; Ye, Shugao; Liu, Feng; Huang, Jian; Ji, Yong; Liu, Dong; Chen, Jingyu (Frontiers in Surgery, 2021)
Background: Destroyed lung can cause mediastinal displacement and asymmetric chest deformity. Reports on bilateral lung transplantation (LT) to treat destroyed lung and asymmetric chest deformity are rare. This study presents our surgical experience of bilateral LT among patients with destroyed lung and asymmetric chest deformity. Methods: Six patients with destroyed lung and asymmetric chest deformity who underwent bilateral LT at our center from 2005 to 2020 were included in the study. Demographic data, technical data, perioperative details, and short-term follow-up data were reviewed. Results: Three patients underwent bilateral LT via anterolateral incisions in the lateral position without sternal transection, while three patients underwent bilateral LT via clam-shell incisions in the supine position with sternal transection. Only one patient required intraoperative extracorporeal membrane oxygenation. Four patients underwent size-reduced LT. In the other two patients, we restored the mediastinum by releasing mediastinal adhesions to ensure maximal preservation of the donor lung function. Patients in the lateral position group had a higher volume of blood loss, longer operation time, and longer postoperative in-hospital stay than those in the supine position group. However, these differences were not statistically significant. Postoperative computed tomography in the supine position group revealed that the donor lungs were well expanded and the mediastina were in their original positions. Conclusions: Although bilateral LT in patients with destroyed lung and asymmetric chest deformity is high risk, with sufficient preoperative preparation and evaluation, it is safe and feasible to perform bilateral LT for selected patients. For patients without severe chest adhesions, releasing the mediastinal adhesions and restoring the mediastinum through a clam-shell incision in the supine position is a simple and effective method to maximally preserve the donor lung function without pneumonectomy or lobectomy.